Investigate Spectroscopic Experimental and Theoretical Model for Hemoglobin Nanoscale Solution (Baghdad Science Journal, 2024)
In the current study, haemoglobin analytes dissolved in a special buffer (KH2PO4(1M), K2HPO4(1M)) with pH of 7.4 were used to record absorption spectra measurements with a range of concentrations from (10-8 to 10-9) M and an absorption peak of 440nm using Broadband Cavity Enhanced Absorption Spectroscopy (BBCEAS) which is considered a simple, low cost, and robust setup. The principle work of this technique depends on the multiple reflections between the light source, which is represented by the Light Emitting Diode 3 W, and the detector, which is represented by the Avantes spectrophotomer. The optical cavity includes two high reflectivity  ≥99%  dielectric mirrors (diameter 25mm, radius of curvature 100mm) and a quartz cuvette  1 cm  to put the samples in the system. This system is also composed of some lenses, aires, and optical fibres to transfer the light from the light source to the optical cavity and after that to the detector. This setup is considered ~3-fold more sensitive when it is compared with another spectroscopic technique as it reduces the effect of noise due to fluctuations in the light intensity. Additionally, the theoretical study estimated the absorption spectra of the haemoglobin concentrations using Table Curve 2D software. The absorption spectra curve was fitted using a suitable curve-fitting equation for these spectra, which was represented by the Gaussian function. The similarity of the theoretical and practical spectra demonstrated that the estimated models can replace the experimental measurements, which leads to a reduction in the cost and time required for the absorption spectroscopy measurements